Properties and Configurations of B-N Co-Doped ZnO Nanorods Fabricated on ITO/PET Substrate - Jiang, Jianchao; Jiang, Liyun; Rong, Ping; Wu, Kechen; Yang, Qingqing; Yu, Qi (Frontiers in Energy Research, 2021)
Based on flexible materials, optoelectronic devices with optoelectronic technology as the core and flexible electronic devices as the platform are facing new challenges in their applications, including material requirements based on functional electronic devices such as lightness, thinness, and impact resistance. However, there is still a big gap between the current preparation technology of flexible materials and practical applications. At present, the main factors restricting the more commercial development of flexible materials include preparation conditions and performance. In this work, B-N co-doped ZnO nanorod arrays (NRAs) were successfully synthesized on the polyethylene terephthalate (PET) substrate coated with indium tin oxide (ITO) by the hydrothermal method. Based on the density functional theory, the effect of B-N co-doping on the electronic structure of ZnO was calculated; the incorporation of B and N led to an increase in the lattice constant of ZnO. The B-N co-doped ZnO has obvious rectification characteristics with the positive conduction voltage of 2 V in the I–V curve.